Empowering the Green Innovation Machine - Reinhilde Veugelers (Intereconomics, 2016)
An important insight from the economic analysis of the effectiveness of public intervention for green innovations is the complementarity between policy instruments, indicating the need for an adequate policy mix of instruments rather than a focus on individual instruments. The evidence provides little support for the efficacy of single instruments, like subsidies, when used in isolation. For the EU, the biggest challenge for its green technology policy is the lack of a sufficiently high carbon price.
Keywords: 330; EU-Forschungspolitik; Innovation; EU-Umweltpolitik; EU-Emissionshandel